Obtention and Characterization of Polypropylene, Calcium Carbonate and Poly(ethylene-co-vinyl acetate) Composites - Alberton, Josué; Martelli, Silvia Maria; Soldi, Valdir (Journal of Research Updates in Polymer Science, 2012)
In the increasingly competitive market, the survival of the industries that manufacture components or pieces of polymer is strictly linked to the reduction of production costs. An alternative could be the use of composites of polypropylene, calcium carbonate and poly(ethylene-co-vinyl acetate) for the production of thermoplastics sheets. The thermoplastics sheets obtained by extrusion and co-extrusion processes were characterized through the chemical, physical, thermal, mechanical and morphological characteristics of materials, enabling the performance analysis of the production processes and application to the design of components or parts. The results showed that the addition of 30 wt% CaCO3-EVA increased the thermal stability of polypropylene (PP) around 32°C, decreasing the processing temperature of composites in 15°C, also by decreasing the crystallinity of the polymer from 43% to 30% and the deflection temperature of plastics under flexural load in the edgewise position (DTUL) from 122°C to 107°C. Regarding to the mechanical tests, the yield stress of the composites obtained by extrusion and co-extrusion processes decreased with the addition of CaCO3-EVA. According with the obtained results, we suggest that PP/CaCO3-EVA composites could be used in the production of polymeric parts or components where tensile strengths higher than 25 MPa are not required and for service temperatures between 30°C and 70°C.